An Approach to Rationalisation of Manpower and Administrative Planning at Range Level in Forest Departments - Kinhal, G. A. (Indian Forester, 1999)
As per requirement of the State Forest administrative units, the creation of posts and much needed job satisfaction will enhance the efficiency of the employees and also help in managing the forests better.